POLEMIC CONCERNING IMPLEMENTATION OF NEW ACADEMIC YEAR 2020/2021 DURING THE PANDEMIC OF COVID-19 IN DETIK.COM, KOMPAS.COM, AND CNNINDONESIA.COM - Zainal Abidin Achmad; Yustika Aini Arrochmah (JARES (Journal of Academic Research and Sciences), 2021)
The Minister of Education and Culture Nadiem Makarim already announced the guidelines for implementing the new school academic year 2020, on June 15, 2020. The execution of the new academic year during the COVID-19 pandemic reaps many pros and cons of several groups. Because many argue that the curriculum explanation in the pandemic period has not detailed, and the fulfillment of the quality of education can not run one hundred percent. Furthermore, the COVID-19 pandemic is still in the peak stages, so it is very worrying if it continues to open the school in the middle of this pandemic. This research uses Robert N. Entman`s Framing Model analysis method with a qualitative approach. The subjects in this research are online media detik.com, kompas.com, and CNNIndonesia.com. This study aims to describe the framing of reporting the implementation of the new school academic year 2020 during the COVID-19 pandemic in online media detik.com, kompas.com, and CNNIndonesia.com is reporting the execution of the new school academic year 2020 during the COVID-19 pandemic. The result of this study indicate that (1) Detik.com, Kompas.com, and CNNIndonesia.com generate public opinion movements which focus on the problem factors that hinder the implementation of the new academic year 2020/2021 during the COVID-19 pandemic, (2) The media coverage by CNNIndonesia.com do not use elements treatment recommendation, (3) Many reports that discuses the type of curriculum during the COVID-19 pandemic.